FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN POLA KONSUMSI IKAN SISWA SEKOLAH DASAR NEGERI 060919 DI KECAMATAN MEDAN SUNGGAL TAHUN 2015 - Asih Monica; Jumirah .; Albiner Siagian (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
Fish is a source of good protein for the growth. The lower of fish consumption of the student of elementary school is a problem caused by any factors. The objective of this research is to study factors related to the fish comsumption pattern of the student of elementary school of SD Negeri 060919 in subdistrict of Medan Sunggal 2015. The method of research is an analytic survey with cross sectional design. The sample is 44 students by purposive sampling method. The species of fish, the number of fish and frequency of fish consumption is indicated by using recall and food frequency questionnaire form. The factors related to the fish comsumption such as knowledge, social culture, economic and support of mother is indicated by using questionnaire form. The result indicated that as many as 15 persons (34,1%) student of elementary school consumed fish that lives in middle water, as many as 23 persons (52,3%) student the number of consumed fish is in good category and as many as 13 persons (29,5%) student frequency of fish consumption in medium category. The result of Chi Square test indicated that there is a correlation of the knowledge and the number of consumed fish (p=0,0001), social culture and the number of consumed fish (p=0,005), economic and the number of consumed fish (p=0,0001), and support of mother and the number of consumed fish (p=0,001). The school also suggested to build a matual cooperation with puskesmas at nutrition extension and Education office to build a matual cooperation with the Agricultural and Marine office of Medan to support the program of Fish Consumption. Keywords : fish consumption, social culture, student of elementary school